Penggunaan Kurikulum Serta Penanaman Nilai dan Spiritual Siswa - Atifah Hanum; Annas Annas (Indonesian Journal of Learning Education and Counseling, 2019)
This study aims to describe the use of the curriculum in SMA N 1 Semanu as well as knowing the planting values ??and spiritual students. The method used is a qualitative method with direct interviews with teachers for guidance and counseling. The results are that the curriculum used in SMA N 1 Semanu has two, namely for grades 10 and 11 using K13, while for class 12 uses KTSP. Cultivation of students' values ??and spirituality in guidance and counseling was carried out with individual and classical guidance, while the material presented was related to motivation to learn, career, positive attitude of students, and build a generation of Muslims. In addition to the material presented also moral values, the impact of adolescent association, appearance and attitudes of women, and others delivered by subject teachers on Fridays specifically for female students. The value of nationalism is played by national songs. In other aspects, namely regarding the value of discipline, students are taught through extracurricular activities, namely scouts.